Variation of normal condyle shape based on gender in panoramic radiographs - Sri Wigati Mardi Mulyani; Eha Renwi Astuti; Otty Ratna Wahyuni; Ramadhan Hardani Putra; Aga Satria Nurrachman; Nastiti Faradilla Ramadhani; Farah Tariza Harlens; Lailatul Hikmah Mazlan (Ikatan Radiologi Kedokteran Gigi Indonesia, 2023)
Objectives: To find out information about variations in the normal shape of the condyles based on gender using panoramic radiographic observations and to find out the frequency data for variations in the normal shape of the condyles. Materials and Methods: This is a descriptive observational research using 122 panoramic radiographs as secondary data. The panoramic image consisted of 61 male samples and 61 female samples. The condyles were observed by describing the condyle shapes on the right and left sides. Observation of the shape of the condyle was carried out by three observers. Then, the data were tested for reliability by using the Intraclass Correlation Coefficient to equalize the perceptions of the three observers. Results: The reliability test using ICC obtained a score > 0.9 which means very good reliability. The most commonly found condyles shape is round and there are differences in shape between the right and left condyles in both males and females. Conclusion: The most common variation of the normal shape of the condyle found in both males and females is round on the right and left sides.